Batik Blimbing Malangan MSME’s Internationalization Strategy in Entering the Malaysian Market - Ranni Endriana Putri; Nur Luthfi Hidayatullah (Jurnal Ilmu Sosial Politik dan Humaniora (JISORA), 2026)
This study aims to describe Batik Blimbing Malangan’s internationalization strategy in marketing its products in the Malaysian market, as well as identify challenges, opportunities, and product characteristics that become the key strengths. Batik Blimbing Malangan is a Micro, Small, and Medium Enterprise (MSME) producing Batik fabric with original cultural design from Malang, Indonesia. This research used a qualitative approach with a case study method, and data collection through in-depth interviews, observation, and documentation. The results show that Batik Blimbing Malangan adopts various strategies to enter the international market, including digital marketing optimization, active participation in international exhibitions, creative collaboration with local designers, and the use of halal certification as an added value. The main characteristic of the product lies in the original design of Malang Mask, Star fruit Flower, bright colors, and the use of electric batik technology. Batik Blimbing Malangan’s designs are perceived as a representation of local culture that has a strong appeal in the Malaysian market, which has similar cultural affinity and religious values. The findings confirm that the successful internationalization of culture-based MSMEs relies heavily on the synergy between cultural identity preservation, product innovation, and adaptability to global market dynamics. This study contributes to the development of export strategies for cultural MSMEs in Indonesia.